Nutrients, Fiber Fraction, and In Vitro Fiber Digestibility of Brown-Midrib Sorghum Mutant Lines Affected by The Maturity Stages - Sriagtula, R.; Karti, P. D. M. H.; Abdullah, L.; Supriyanto; Astuti, D. A.; Zurmiati (Tropical Animal Science Journal, 2021)
The mutant line of Brown-midrib sorghum has lower lignin content than conventional sorghum. The objectives of this research were to investigate the effects of plant maturity stages at harvest times on nutrient, fiber fraction, tannin content, volatile fatty acids (VFA) production, and in vitro fiber digestibility of mutant lines of Brown Midrib (BMR) sorghum. This research was arranged into a complete block design with a factorial arrangement in three replications. The first factor was a line of BMR sorghum consisted of 3 levels, i.e., Patir 3.1 (non-BMR line/control), Patir 3.2 (BMR line), and Patir 3.7 (BMR line). The second factor was the generative stages of sorghum consisted of 3 levels, i.e., flowering stage, soft-dough stage, and hard-dough stage. The observed variables were nutrient, fiber fraction, tannin content, in vitro rumen fluid characteristics, VFA proportion, acetate: propionate (A:P) ratio, and in vitro fiber-fraction digestibility (IVFFD). Data were analyzed by Analysis of Variance (ANOVA) and Duncan’s Multiple Range Test (DMRT). No interaction between sorghum-mutant lines and harvest time on nutrient contents, except on total digestible nutrients (TDN), tannin, and VFA. The factor of sorghum-mutant line affected (p